Valoración a la propiedad, planta y equipos en las empresas del sector camaronero - Aspiazu Echeverría, Jimmy Henry (2021)
This research, which is called "Property Valuation, Plant Equipment in Shrimp Sector Companies", focuses its study on a group of companies in the shrimp sector, and the correct application of the NIC (International Accounting Standards) and IFRS (International Financial Information Standards), and determine that the accounting treatment applied is being recorded in accordance with the regulations established for this purpose. NIC 16. In order to carry out a prior exhaustive study of NIC 16, the purpose is to establish it from the Theoretical and conceptual point of view, how they can be put into practice with the information collected from the shrimp farm's accounting books, in order to apply and verify the incidence of property, plant and equipment under the application of international standards in the financial statements............